Common Security and Defence Policy: A Legal Framework for Developing the European Defence Industry - Masło, Krzysztof (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
The European Union’s (EU) Common Security and Defence Policy (CSDP) is a component of its Common Foreign and Security Policy (CFSP). It was established in the Maastricht Treaty on European Union, which included a provision for the gradual introduction of a common defence policy that could eventually lead to a common defence framework. The CFSP emerged from the need to enhance the EU’s political identity on the international arena and assert Europe’s independence in the post-Cold War era. Simultaneously, it remains one of the few areas of competence that exclusively belongs to Member States, where proposals to deepen integration processes have met with lukewarm responses. However, the Russo-Ukrainian war has prompted the European forum to strengthen cooperation between Member States, particularly in the defence industry sector. The CSDP is regulated only by the Treaty on EU (TEU), while other EU policies are governed by the Treaty on the Functioning of the EU (TFEU). The architects of the Lisbon reform aimed to underscore the distinctiveness of the CSDP from other EU policies, as demonstrated by its legal instruments, decision-making mechanisms, and the nature of EU competences. Cooperation under the CSDP does not fit neatly within the traditional treaty rules governing the division of competences between the EU and its Member States. Fundamental competences in the field of security policy are reserved for Member States, which result from both the TEU and the unambiguous content of Declaration No. 13 on the CFSP. The CSDP’s intergovernmental nature CSDP determines its institutional implementation. It is defined and implemented by intergovernmental EU institutions, particularly the European Council and the Council. The High Representative supported by the European External Action Service and Member States play a key role in its implementation, drawing on both EU and national funds. The competences of the EU’s supranational institutions, particularly the Court of Justice of European Union, are strictly limited in this area. The relationship between the North Atlantic Treaty Organization and the EU was institutionalised in the early 21st century, building on initiatives from the 1990s aimed at promoting greater European responsibility in defence matters. Keywords: Common Foreign and Security Policy (CFSP), CSDP legal basis, Court of Justice of EU (CJEU), decision-making mechanism in the CSDP, North Atlantic Treaty Organization (NATO), Treaty on European Union (TEU)